1997
DOI: 10.1046/j.1526-4610.1997.3703137.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Migraine Visual Aura

Abstract: Visual auras (VAs) of 100 patients with migraine with aura were studied by questionnaire. Visual auras accompanied the patients' first headache (HA) in 39% of patients. Only 19% had VAs with every attack. Patients with VAs over the entire HA history had a high frequency (greater than 50%) of attacks with VA; patients with VA during only part of the HA history had a low frequency (less than 50%) of attacks with VA. The auras occurred exclusively prior to the HA in 57%. The free interval between the end of the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
85
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 16 publications
13
85
1
2
Order By: Relevance
“…In our MWA group, the most common aura symptoms reported were visual and our results were similar to those in previous epidemiologic studies (Lee and Olness 1997;Queiroz et al 1997;Roh et al 1998;Lipton et al 2001). Our subjects reported similar incidences of associated symptoms (phonophobia, nausea, and photophobia) reported from previous studies (Rasmussen 1993;Queiroz et al 1997;Lipton et al 2001;Mattson 2003). The clinical characteristics of migraine was found to be different than the study conducted by Köseo ğlu et al (2003); a higher ratio of phonophobia and a lower ratio of nausea were found in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In our MWA group, the most common aura symptoms reported were visual and our results were similar to those in previous epidemiologic studies (Lee and Olness 1997;Queiroz et al 1997;Roh et al 1998;Lipton et al 2001). Our subjects reported similar incidences of associated symptoms (phonophobia, nausea, and photophobia) reported from previous studies (Rasmussen 1993;Queiroz et al 1997;Lipton et al 2001;Mattson 2003). The clinical characteristics of migraine was found to be different than the study conducted by Köseo ğlu et al (2003); a higher ratio of phonophobia and a lower ratio of nausea were found in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Wilkinson (2004) has reviewed migraine visual aura in the context of other visual hallucinations and suggested how these might relate to the neural mechanism of aura. Queiroz et al (1997) showed that visual aura accompanied the patient's first headache in 39% of patients but only 19% had visual aura with every attack. The free period between visual aura and head pain was <30 min in 75% of cases.…”
Section: Visual Auramentioning
confidence: 99%
“…Disturbances of visual perception are the least frequent and include foggy vision, tunnel vision, the perception of looking through heat waves or water, mosaic, and, rarely, complex visual hallucinations. 49 Sensory, aphasic, and motor aurae occur in 20%, 11%, and 4% of patients, respectively. One establishes a diagnosis of migraine with typical aura when one of these aurae or a homonymous visual disturbance is present.…”
Section: Features Of the Migraine Auramentioning
confidence: 99%